THE PROLIFERATIVE ABILITY OF CISTANCHE DESERTICOLA AND ANALYSIS OF THE QUANTITATIVE CONTENT OF FLAVONOIDS IN CELL CULTURE - Rakhimzhanova , A.O.; Bekkuzhina , S.S.; Kali , B.R.; Argumbayeva , A.K.; Tussipkan , D.; Manabayeva , Sh.A. (Eurasian Journal of Applied Biotechnology, 2025)
Cistanche deserticola contains a significant amount of flavonoids and other valuable bioactive compounds, making it a promising subject for pharmacological research, as well as the development of new pharmaceutical drugs and biologically active supplements. The introduction of C. deserticola into in vitro culture and the establishment of suspension cell lines with high proliferative activity opens new perspectives for sustainable and efficient biomass production while preserving its unique properties. As a result of our research, callus lines were obtained with varying colors, from light to dark brown. This fact indicates the heterogeneity of the cell masses, which is related to the peculiarities of metabolite synthesis under in vitro conditions. For the first time, we have obtained cell lines of С. deserticola and studied their stable proliferation in suspension culture. Quantitative analysis of the bioactive compounds content in the suspension cultures, performed by HPLC-MS using standards of apigenin, rutin, and quercetin, revealed a decrease in flavonoid content in the cell cultures with dark color. This may indicate changes in the metabolic activity of the cells as they differentiate. The obtained data may be significant for the targeted regulation of the synthesis of bioactive compounds in С. deserticola cell culture.